Rampes: Unveiling the Ideal Counselor Traits in the Sanghyang Siksakandang Karesian Manuscript - Hidayat, Ade; Supriatna, Mamat (Jurnal Kajian Bimbingan dan Konseling, 2025)
This study aims to describe the ideal characteristics of a counselor based on the values contained in the Sanghyang Siksakandang Karesian (SSK) manuscript. A hermeneutic approach was employed to interpret the meaning of the text from the perspective of guidance and counseling grounded in local wisdom. The findings indicate that the concept of Rampes, mentioned 24 times in the manuscript, serves as the foundation for shaping a counselor’s professional, moral, and integrative character. This concept comprises three dimensions: (1) Bakti, which reflects religious awareness as a creature of God as well as a commitment to ethical behavior; (2) Wastu Siwong, a combination of knowledge, skills, and ethics that fosters integrity and professional competence; and (3) Pangimbuh ning Twah, encompassing social and personal competencies that support success in family and community relationships. These three dimensions are interrelated and form a holistic Rampes counselor profile. By internalizing these dimensions, counselors are expected to provide guidance services that are effective, empathetic, and aligned with local cultural values. These findings contribute to the development of guidance and counseling sciences based on local wisdom and strengthen the relevance of culturally grounded approaches in professional counseling practice.